Population Genomic Analyses Reveal Geographic Structure in Rhizoctonia solani AG1 ‐ IA Isolates Associated With Agronomic Crops - Juanita Gil; Kensy Rodriguez‐Herrera; Vanina Castroagudin; Felipe Dalla Lana; Camila P. Nicolli; Xin‐Gen Zhou; Sara Thomas‐Sharma; Terry Spurlock; Jim C. Correll; Pierre Gladieux; Alejandro Rojas (Molecular Ecology, 2026)
Soilborne fungal pathogens threaten food security, but limited knowledge of their population biology, including genetic variability and population structure, hinders the development of effective strategies to prevent crop losses. Rhizoctonia solani AG‐1 is a significant soilborne pathogen worldwide, divided into subgroups based on host range and molecular diversity. Rhizoctonia solani AG1‐IA causes sheath blight in rice and aerial blight in soybean, two devastating diseases in these economically important crops. Rice and soybean are often grown in rotation, leading to the buildup of inoculum in the fields over cropping seasons. Monitoring the genetic variability and structure of R. solani AG1‐IA is critical to understand the population biology of the pathogen and aid in disease management practices, including the screening and development of new resistant cultivars. A total of 145 isolates of R. solani collected between 1993 and 2022 from different hosts and states in the USA were sequenced. The population genetic structure was inferred with clustering approaches based on approximately two million biallelic single nucleotide polymorphisms (SNPs). Rhizoctonia solani AG1‐IA showed relatively high genetic diversity and little departure from mutation‐drift equilibrium, suggesting that R. solani AG1‐IA is a well‐established, widespread pathogen with a stable demographic history in the USA. While populations had a clear geographic structure, they lacked host specialization, suggesting dispersal is mainly distance limited. Shared ancestry between populations and the discovery of clonal lineages, however, indicated recent connections between geographic areas. Our work provides valuable insights into the evolutionary history and population biology of R. solani AG1‐IA, offering a foundation for developing targeted management strategies and resistant crop varieties.

Heterogeneity of the rice microbial community of the Chinese centuries‐old Honghe Hani rice terraces system - Pascal Alonso; Laurence Blondin; Pierre Gladieux; Frédéric Mahé; Hervé Sanguin; Romain Ferdinand; Denis Filloux; Eric Desmarais; Frédérique Cerqueira; Baihui Jin; Huichuan Huang; Xiahong He; et al. (Environmental Microbiology, 2020)
Summary The Honghe Hani rice terraces system (HHRTS) is a traditional rice cultivation system where Hani people cultivate remarkably diverse rice varieties. Recent introductions of modern rice varieties to the HHRTS have significantly increased the severity of rice diseases within the terraces. Here, we determine the impacts of these recent introductions on the composition of the rice‐associated microbial communities. We confirm that the HHRTS contains a range of both traditional HHRTS landraces and introduced modern rice varieties and find differences between the microbial communities of these two groups. However, this introduction of modern rice varieties has not strongly impacted the overall diversity of the HHRTS rice microbial community. Furthermore, we find that the rice varieties (i.e. groups of closely related genotypes) have significantly structured the rice microbial community composition (accounting for 15%–22% of the variance) and that the core microbial community of HHRTS rice plants represents less than 3.3% of all the microbial taxa identified. Collectively, our study suggests a highly diverse HHRTS rice holobiont (host with its associated microbes) where the diversity of rice hosts mirrors the diversity of their microbial communities. Further studies will be needed to better determine how such changes might impact the sustainability of the HHRTS.

Widespread selective sweeps throughout the genome of model plant pathogenic fungi and identification of effector candidates - H. Badouin; P. Gladieux; J. Gouzy; S. Siguenza; G. Aguileta; A. Snirc; S. Le Prieur; C. Jeziorski; A. Branca; T. Giraud (Molecular Ecology, 2017)
Identifying the genes underlying adaptation, their distribution in genomes and the evolutionary forces shaping genomic diversity are key challenges in evolutionary biology. Very few studies have investigated the abundance and distribution of selective sweeps in species with high‐quality reference genomes, outside a handful of model species. Pathogenic fungi are tractable eukaryote models for investigating the genomics of adaptation. By sequencing 53 genomes of two species of anther‐smut fungi and mapping them against a high‐quality reference genome, we showed that selective sweeps were abundant and scattered throughout the genome in one species, affecting near 17% of the genome, but much less numerous and in different genomic regions in its sister species, where they left footprints in only 1% of the genome. Polymorphism was negatively correlated with linkage disequilibrium levels in the genomes, consistent with recurrent positive and/or background selection. Differential expression in planta and in vitro, and functional annotation, suggested that many of the selective sweeps were probably involved in adaptation to the host plant. Examples include glycoside hydrolases, pectin lyases and an extracellular membrane protein with CFEM domain. This study thus provides candidate genes for being involved in plant–pathogen interaction (effectors), which have remained elusive for long in this otherwise well‐studied system. Their identification will foster future functional and evolutionary studies, in the plant and in the anther‐smut pathogens, being model species of natural plant–pathogen associations. In addition, our results suggest that positive selection can have a pervasive impact in shaping genomic variability in pathogens and selfing species, broadening our knowledge of the occurrence and frequency of selective events in natural populations.

Genomic signatures of adaptation to wine biological ageing conditions in biofilm‐forming flor yeasts - A. L. Coi; F. Bigey; S. Mallet; S. Marsit; G. Zara; P. Gladieux; V. Galeote; M. Budroni; S. Dequin; J. L. Legras (Molecular Ecology, 2017)
The molecular and evolutionary processes underlying fungal domestication remain largely unknown despite the importance of fungi to bioindustry and for comparative adaptation genomics in eukaryotes. Wine fermentation and biological ageing are performed by strains of S. cerevisiae with, respectively, pelagic fermentative growth on glucose and biofilm aerobic growth utilizing ethanol. Here, we use environmental samples of wine and flor yeasts to investigate the genomic basis of yeast adaptation to contrasted anthropogenic environments. Phylogenetic inference and population structure analysis based on single nucleotide polymorphisms revealed a group of flor yeasts separated from wine yeasts. A combination of methods revealed several highly differentiated regions between wine and flor yeasts, and analyses using codon‐substitution models for detecting molecular adaptation identified sites under positive selection in the high‐affinity transporter gene ZRT 1 . The cross‐population composite likelihood ratio revealed selective sweeps at three regions, including in the hexose transporter gene HXT 7 , the yapsin gene YPS 6 and the membrane protein coding gene MTS 27 . Our analyses also revealed that the biological ageing environment has led to the accumulation of numerous mutations in proteins from several networks, including Flo11 regulation and divalent metal transport. Together, our findings suggest that the tuning of FLO 11 expression and zinc transport networks are a distinctive feature of the genetic changes underlying the domestication of flor yeasts. Our study highlights the multiplicity of genomic changes underlying yeast adaptation to man‐made habitats and reveals that flor/wine yeast lineage can serve as a useful model for studying the genomics of adaptive divergence.

Globally invading populations of the fungal plant pathogen V erticillium dahliae are dominated by multiple divergent lineages - Dylan P. G. Short; Suraj Gurung; Pierre Gladieux; Patrik Inderbitzin; Zahi K. Atallah; Franco Nigro; Guoqing Li; Seher Benlioglu; Krishna V. Subbarao (Environmental Microbiology, 2015)
Summary The spread of aggressive fungal pathogens into previously non‐endemic regions is a major threat to plant health and food security. Analyses of the spatial and genetic structure of plant pathogens offer valuable insights into their origin, dispersal mechanisms and evolution, and have been useful to develop successful disease management strategies. Here, we elucidated the genetic diversity, population structure and demographic history of worldwide invasion of the ascomycete V erticillium dahliae , a soil‐borne pathogen, using a global collection of 1100 isolates from multiple plant hosts and countries. Seven well‐differentiated genetic clusters were revealed through discriminant analysis of principal components ( DAPC ), but no strong associations between these clusters and host/geographic origin of isolates were found. Analyses of clonal evolutionary relationships among multilocus genotypes with the e BURST algorithm and analyses of genetic distances revealed that genetic clusters represented several ancient evolutionary lineages with broad geographic distribution and wide host range. Comparison of different scenarios of demographic history using approximate B ayesian computations revealed the branching order among the different genetic clusters and lineages. The different lineages may represent incipient species, and this raises questions with respect to their evolutionary origin and the factors allowing their maintenance in the same areas and same hosts without evidence of admixture between them. Based on the above findings and the biology of V . dahliae , we conclude that anthropogenic movement has played an important role in spreading V . dahliae lineages. Our findings have implications for the development of management strategies such as quarantine measures and crop resistance breeding.

The population biology of fungal invasions - P. Gladieux; A. Feurtey; M. E. Hood; A. Snirc; J. Clavel; C. Dutech; M. Roy; T. Giraud (Molecular Ecology, 2015)
Fungal invasions are increasingly recognized as a significant component of global changes, threatening ecosystem health and damaging food production. Invasive fungi also provide excellent models to evaluate the generality of results based on other eukaryotes. We first consider here the reasons why fungal invasions have long been overlooked: they tend to be inconspicuous, and inappropriate methods have been used for species recognition. We then review the information available on the patterns and mechanisms of fungal invasions. We examine the biological features underlying invasion success of certain fungal species. We review population structure analyses, revealing native source populations and strengths of bottlenecks. We highlight the documented ecological and evolutionary changes in invaded regions, including adaptation to temperature, increased virulence, hybridization, shifts to clonality and association with novel hosts. We discuss how the huge census size of most fungi allows adaptation even in bottlenecked, clonal invaders. We also present new analyses of the invasion of the anther‐smut pathogen on white campion in North America, as a case study illustrating how an accurate knowledge of species limits and phylogeography of fungal populations can be used to decipher the origin of invasions. This case study shows that successful invasions can occur even when life history traits are particularly unfavourable to long‐distance dispersal and even with a strong bottleneck. We conclude that fungal invasions are valuable models to contribute to our view of biological invasions, in particular by providing insights into the traits as well as ecological and evolutionary processes allowing successful introductions.

Postglacial recolonization history of the E uropean crabapple ( Malus sylvestris M ill.), a wild contributor to the domesticated apple - A. Cornille; T. Giraud; C. Bellard; A. Tellier; B. Le Cam; M. J. M. Smulders; J. Kleinschmit; I. Roldan‐Ruiz; P. Gladieux (Molecular Ecology, 2013)
Understanding the way in which the climatic oscillations of the Quaternary Period have shaped the distribution and genetic structure of extant tree species provides insight into the processes driving species diversification, distribution and survival. Deciphering the genetic consequences of past climatic change is also critical for the conservation and sustainable management of forest and tree genetic resources, a timely endeavour as the Earth heads into a period of fast climate change. We used a combination of genetic data and ecological niche models to investigate the historical patterns of biogeographic range expansion of a wild fruit tree, the E uropean crabapple ( M alus sylvestris ), a wild contributor to the domesticated apple. Both climatic predictions for the last glacial maximum and analyses of microsatellite variation indicated that M . sylvestris experienced range contraction and fragmentation. Bayesian clustering analyses revealed a clear pattern of genetic structure, with one genetic cluster spanning a large area in Western E urope and two other genetic clusters with a more limited distribution range in Eastern E urope, one around the Carpathian Mountains and the other restricted to the Balkan P eninsula. Approximate Bayesian computation appeared to be a powerful technique for inferring the history of these clusters, supporting a scenario of simultaneous differentiation of three separate glacial refugia. Admixture between these three populations was found in their suture zones. A weak isolation by distance pattern was detected within each population, indicating a high extent of historical gene flow for the E uropean crabapple.

Migration patterns and changes in population biology associated with the worldwide spread of the oilseed rape pathogen Leptosphaeria maculans - A. DILMAGHANI; P. GLADIEUX; L. GOUT; T. GIRAUD; P. C. BRUNNER; A. STACHOWIAK; M.‐H. BALESDENT; T. ROUXEL (Molecular Ecology, 2012)
Pathogen introductions into novel areas can lead to the emergence of new fungal diseases of plants. Understanding the origin, introduction pathways, possible changes in reproductive system and population size of fungal pathogens is essential in devising an integrated strategy for the control of these diseases. We used minisatellite markers to infer the worldwide invasion history of the fungal plant pathogen Leptosphaeria maculans , which causes stem canker (blackleg) of oilseed and vegetable brassicas. Clustering analyses partitioned genotypes into distinct populations corresponding to major geographic regions, along with two differentiated populations in Western Canada. Comparison of invasion scenarios using Approximate Bayesian Computation suggested an origin of the pathogen in the USA, the region where epidemics were first recorded, and independent introductions from there over the last few decades into Eastern Canada (Ontario), Europe and Australia. The population in Western Canada appeared to be founded from a source in Ontario and the population in Chile resulted from an admixture between multiple sources. A bottleneck was inferred for the introduction into Western Canada but not into Europe, Ontario or Australia. Clonality appeared high in Western Canada, possibly because environmental conditions there were less conducive to sexual reproduction. Leptosphaeria maculans is a model invasive pathogen with contrasting features in different regions: shallow population structure, high genetic variability and regular sexual recombination in some regions, by comparison with reduced genetic variability, high rates of asexual multiplication, strong population structure or admixture in others.